An overview of sports field drainage: Development of experimental investigation methodology - Kesgin, Erdal; Gezici, Kadir; Agaccioglu, Hayrullah (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2023)
Hydrological evaluation of soil-water relationships for infiltration and drainage is a complex issue. Within the scope of this study, the significance of the experimental studies for the drainage design of sports fields is emphasized. In addition, a standard technique was tried to develop due to the lack of absence of certain specifications and inaccurate designs mostly based on the traditional experience regarding sports field drainage. The essential circumstances for the success of the experimental studies were presented and a sample drainage section was compared. As a result of the experimental studies, it was understood that the pattern of the hyetograph applied to the system and the layer thicknesses of the drainage section were highly effective on the parameters of the output flow hydrograph. Due to the lack of studies for sports field drainage that their mechanisms were not clearly revealed, the presented study is significant in term of developing a new perspective and procedure to the relevant field.
Keywords: Sports field; drainage; rainfall simulator; SEDIMENT TRANSPORT; SOIL; SAND; LAYER; SIZE; Engineering